2021
DOI: 10.3389/fmicb.2021.633510
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Manipulation of Non-tuberculosis Mycobacteria

Abstract: Non-tuberculosis mycobacteria (NTMs) comprise a large group of organisms that are phenotypically diverse. Analysis of the growing number of completed NTM genomes has revealed both significant intra-genus genetic diversity, and a high percentage of predicted genes that appear to be unique to this group. Most NTMs have not been studied, however, the rise in NTM infections in several countries has prompted increasing interest in these organisms. Mycobacterial research has recently benefitted from the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…In turn, this enables the screening of only small numbers of clones to obtain the desired mutants. Indeed, we report an efficiency rate of 1.1%–9.3% using this two-plasmid system for the disruption of a single gene, which is at least 10 2 –10 4 more efficient than rates reported for homologous recombination ( 9 12 ). Compared to traditional approaches where success is limited due to the occurrence of spontaneous background resistance and low efficiency of homologous recombination, the high frameshift frequency suggests that CRISPR/Cas9 is an important addition to the toolbox for genetic manipulation in M. abscessus .…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…In turn, this enables the screening of only small numbers of clones to obtain the desired mutants. Indeed, we report an efficiency rate of 1.1%–9.3% using this two-plasmid system for the disruption of a single gene, which is at least 10 2 –10 4 more efficient than rates reported for homologous recombination ( 9 12 ). Compared to traditional approaches where success is limited due to the occurrence of spontaneous background resistance and low efficiency of homologous recombination, the high frameshift frequency suggests that CRISPR/Cas9 is an important addition to the toolbox for genetic manipulation in M. abscessus .…”
Section: Discussionmentioning
confidence: 58%
“…Current methods for genetically engineering M. abscessus have been largely limited to suboptimal and tedious recombination-based methods due to the high rates of spontaneous background antibiotic resistance. These methods are inefficient, necessitating the selection of numerous colonies to identify the correct mutants, or ineffective, where the desired clone cannot be obtained ( 9 12 ). Meanwhile, CRISPR/Cas9 has revolutionized the field of genome editing but has only recently been adapted for use in mycobacteria for this purpose ( 19 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gene manipulation has been widely developed during these last two decades, mainly in M. tuberculosis and M. smegmatis , through the generation of knockout mutants and the development of regulated expression systems, which have been instrumental to our understanding of pathogenic mechanisms and to demonstrate the essentiality of genes encoding drug targets. However, functional genomics tools are limited in M. abscessus , with mutagenesis approaches developed in other species often proving to be challenging to adopt in M. abscessus ( 17 , 18 ). Despite these difficulties, recent studies have reported the successful use of CRISPR/Cas-based systems to inducibly silence the expression of targeted genes in M. abscessus ( 19 ).…”
Section: Introductionmentioning
confidence: 99%